2009
DOI: 10.1093/ndt/gfn708
|View full text |Cite
|
Sign up to set email alerts
|

Cellular phenotypes in human stenotic lesions from haemodialysis vascular access

Abstract: Our results demonstrate that contractile smooth muscle cells, myofibroblasts, fibroblasts and macrophages all play a role in the pathogenesis of dialysis access dysfunction (grafts and fistulae). Targeting these specific cell types might result in the development of novel therapeutic paradigms for haemodialysis vascular access dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 27 publications
4
119
1
3
Order By: Relevance
“…The average CHADS2 score was 1.6 1 for AF patients who developed VAT and 2.0 1.2 for AF patients without VAT events ( p 0.28). In addition, the CHADS2 score was not correlated to serum CRP levels in our study ( p 0.23, Pearson's correlation analysis), which can be explained by the different nature of thromboembolic events and VAT [26][27][28] . Neointimal hyperplasia may play a key role in the development of VAT, but not in thromboembolic events among AF patients.…”
Section: Discussioncontrasting
confidence: 66%
“…The average CHADS2 score was 1.6 1 for AF patients who developed VAT and 2.0 1.2 for AF patients without VAT events ( p 0.28). In addition, the CHADS2 score was not correlated to serum CRP levels in our study ( p 0.23, Pearson's correlation analysis), which can be explained by the different nature of thromboembolic events and VAT [26][27][28] . Neointimal hyperplasia may play a key role in the development of VAT, but not in thromboembolic events among AF patients.…”
Section: Discussioncontrasting
confidence: 66%
“…Recurrent stenosis in AVGs is mostly attributed to the development of occlusive IH at the graft-vein anastomosis (15,54). As expected, the types of cells isolated from graft IH lesions include not only the typical myofibroblasts characteristic of AVF lesions and a small proportion of contractile VSMCs (,10%) but also, an abundance of macrophages (54).…”
Section: Preexisting Vascular Pathology and Avg Outcomesmentioning
confidence: 53%
“…These studies emphasized the profound histologic differences between preexisting and postoperative IH ( Figure 1). Postoperative lesions are recognized as eccentric concentrations of myofibroblasts in the intima of AVFs and AVGs (9,10,15), whereas the preexisting venous pathology consists of concentric accumulations of both myofibroblasts and contractile VSMCs underneath the endothelial line (10,13). The National Institute of Diabetes and Digestive and Kidney Diseases-funded multicenter, observational Hemodialysis Fistula Maturation (HFM) Study confirmed the high prevalence of preexisting IH in veins used to create an AVF in 370 patients with CKD.…”
Section: Ih Pathobiology Of Preexisting Ihmentioning
confidence: 90%
“…1,[9][10][11] The formation of neointima results from endothelial activation, 23 inflammation, 17,19 increased cell proliferation and migration, and matrix accumulation. 35 The formation of excessive neointima plays a major role in the maturational failure of AVFs, in which the AVFs may never fully acquire the capacity to accommodate and sustain the heightened rate of blood flow required for effective dialysis; it also accounts for late AVF failure after variable periods of adequate function. 1,34 In the current studies we have expanded on our previous observations and demonstrated that ETS-1 expression is increased in a mouse model of AVF as well as in human AVFs.…”
Section: Discussionmentioning
confidence: 99%